The bcl-2/IgH rearrangement in a population of 204 healthy individuals: occurrence, age and gender distribution, breakpoints, and detection method validity - Schmitt, Christina; Balogh, Brigitta; Grundt, Alexander; Buchholtz, Christian; Leo, Albrecht; Benner, Axel; Hensel, Manfred; Ho, Anthony Dick; Leo, Eugen (Leukemia research, 2006)
This study assessed prevalence, frequency, age and gender distribution and breakpoint locations, and detection method validity for the bcl-2/IgH rearrangement in 204 healthy individuals. For this purpose, both classic two-step, nested, semi-quantitative PCR as well as a newly established sequence-specific, hybridization probe-based real-time quantitative PCR (RQ-PCR) were employed and tested for their sensitivity and specificity for detecting t(14;18) positive cells in healthy blood donors. Interestingly, almost a quarter (24%; 39/204) of all healthy individuals carried the translocation, confirming data of one large prior report [Summers KE, Goff LK, Wilson AG, Gupta RK, Lister TA, Fitzgibbon J. Frequency of the Bcl-2/IgH rearrangement in normal individuals: implications for the monitoring of disease in patients with follicular lymphoma. J Clin Oncol 2001;19(2):420-4]. Regarding presence as well as frequency of the translocation, no correlation to age (mean frequency 2.0:104, with a median of <l:104, for <40 years, and mean frequency 1.9:104, with a median of <l:104 for individuals ≥40 years) nor gender was detected. Comparing the two PCR approaches, a 95.1% concordance (194/204) regarding t(14;18) detection was determined for nested and RQ-PCR, with nested PCR being slightly more sensitive (reproducible detection limit l:105 cells versus 1:104; maximum detection limit l:106 versus 1:105). Sequence analysis confirmed individual breakpoints for all samples analyzed (29/29), indicating detection validity for both PCR approaches and ruling out contamination. The breakpoint location distribution pattern appeared to be comparable to the pattern seen with follicular lymphoma (FL) patient collectives. In conclusion, clonal bcl-2/IgH rearrangements are indeed a very frequent observation in healthy individuals, and appear to be independent of age and gender in regard to presence and frequency. This represents a conflicting finding in context of potential biological significance, and presents a potential disruptive factor for minimal residual disease (MRD) monitoring in FL patients. Prospective future trials will have to clarify the biological significance of this important observation.